Statements in stone : monuments and society in Neolithic Brittany - Patton, Mark (Routledge, 1993)
The great stone monuments, or megaliths, of Western Europe have for centuries excited the popular imagination. Recent years have seen an upsurge of interest in megalith studies involving a shift in emphasis away from traditional concerns with typology, chronology and megalithic 'origins' toward attempts to understand the social significance of these monuments and the cultural dimensions of monument construction and ritual.